EVALUASI LAYANAN SIRKULASI PERPUSTAKAAN - Ariyanti, Hilma; Hanum, Atiqa Nur Latifa (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2020)
AbstractThis study discusses the evaluation of circulation services in the Office of Archives and Regional Library of Kubu Raya. This research is motivated by the lack of utilization of circulation services. This has an impact on the satisfaction of librarians in searching for information. The purpose of this study is to describe the evaluation of circulation services and find out the services applied to the Office of Archives and the Regional Library of Kubu Raya Regency. In this thesis, I?am using qualitative methods in a descriptive form. The way I collect data is through interviews, observations, and documentation conducted with 4 (four) informants. The results of this study explain that the stages of input, the stage of the process, and the stage of the output in the evaluation of circulation services, have met the needs of librarians and have been implemented well. But the satisfaction of the librarians must really be considered to improve the image of library services. The results of the evaluation of circulation services indicate the level of satisfaction of users of the services provided by librarians and managers, at the Archives Service and the Regional Library of Kubu Raya Regency.Keywords: Circulation Services, Libraries, Service Evaluation